2013
DOI: 10.3390/wevj6040996
|View full text |Cite
|
Sign up to set email alerts
|

How expensive are electric vehicles? A total cost of ownership analysis.

Abstract: This paper presents a total cost of ownership (TCO) model for three different car segments. The goal is to investigate the cost efficiency of electric vehicles compared to conventional vehicles. All costs that occur during the expected vehicle's lifespan are included: purchase cost, registration tax, vehicle road tax, maintenance, tires and technical control cost, insurance cost, battery leasing cost, battery replacement cost and fuel or electricity cost. Results are shown per vehicle segment and illustrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Analysis of two comparable vehicles, an EV and a gasoline ICE, in typical driving conditions in Trinidad and Tobago, has shown that the EV is beneficial in most metrics. A MATLAB/Simulink 1 A higher rate of depreciation is assumed for the EV given its higher purchase price and the rapid evolution of EV technology, which is assumed to have a negative effect 2 Calculated based on a pump price of $4.97/litre and the energy content of 1 litre of gasoline being 8.9 kWh 3 Maintenance cost estimations were derived from Lebeau et al (2013) [20] simulation model of each vehicle was created and validated with real-world data, proving that the models are representative. A Trinidad & Tobago Drive Cycle was developed and used as the input to the simulation model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of two comparable vehicles, an EV and a gasoline ICE, in typical driving conditions in Trinidad and Tobago, has shown that the EV is beneficial in most metrics. A MATLAB/Simulink 1 A higher rate of depreciation is assumed for the EV given its higher purchase price and the rapid evolution of EV technology, which is assumed to have a negative effect 2 Calculated based on a pump price of $4.97/litre and the energy content of 1 litre of gasoline being 8.9 kWh 3 Maintenance cost estimations were derived from Lebeau et al (2013) [20] simulation model of each vehicle was created and validated with real-world data, proving that the models are representative. A Trinidad & Tobago Drive Cycle was developed and used as the input to the simulation model.…”
Section: Resultsmentioning
confidence: 99%
“…We can calculate the Total Cost of Ownership for the EV and the ICE vehicle, with the timeframe assumed to be 5 years and with similar usage in each case (Table 23). The maintenance cost estimations were derived from Lebeau et al (2013) [20]. Please note that all costs are shown in TTD.…”
Section: Ev Vs Ice Vehicle Cost Of Ownershipmentioning
confidence: 99%
“…Due to the significant progress in the AFV sector, including new engine technologies, new model launches and also a continuously high dependence on public interventionism, it was extremely challenging to forecast the residual value ("RV") of B-EVs, PH-EVs and FC-EVs. The total cost of ownership is also a key aspect in any corporate fleet tender, as it is ultimately not the new-car transaction price but its TCO, which defines the cost competitiveness of a vehicle model versus its competitors [59].…”
Section: Customer Behaviour and Its Impact On Afv Adaptationmentioning
confidence: 99%
“…Thus, there are priority risks that will lead to more efforts in management and attention in the preparation of projects. These are mainly the risks associated with the operational and financial viability of the projects (Lebeau et al, 2013;Vaz, 2015). The identification of risks in the electrification process does not necessarily imply that the project is not viable, but it does bring a warning signal that should be considered in the decision-making process.…”
Section: Risk Matrixmentioning
confidence: 99%
“…Through this strategy, it is possible, for example, to build a more solid electrification process, which will allow reducing technology uncertainties, as well as potentializing the possible benefits of using electric vehicles. It is worth mentioning that electric buses have barriers inherent to all emerging technologies, such as the high cost of implementation and risks associated with the business (Greenpeace, 2016, D'agosto, Gonçalves & Almeida, 2017Slowik, et al, 2018, Lebeau, Lebeau, Macharis & Mierlo, 2013Vaz, 2015). Given the importance of public transport for cities, it is relevant that any modification, especially structural, such as the replacement of the propulsion system, should come up in studies that allow us to glimpse not only the long-term economic and financial viability, but also the technical viability, environmental and social aspects of new transport projects.…”
Section: Introductionmentioning
confidence: 99%